2016
DOI: 10.1021/acs.estlett.6b00444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ultraviolet Photolysis of Monochloramine on 1,4-Dioxane Removal: New Insights into Potable Water Reuse

Abstract: Although chloramines are ubiquitously present during ultraviolet-driven advanced oxidation processes (UV/AOP) that are becoming increasingly important for potable water reuse, the photochemistry of chloramines in treated wastewater, and the associated effects on trace chemical contaminant degradation, are unknown. This study investigated the fundamental radical chemistry involved in monochloramine (NH2Cl) photolysis and its efficiency in degrading 1,4-dioxane using a low-pressure Hg lamp (λ = 254 nm). These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 41 publications
1
89
0
1
Order By: Relevance
“…Therefore, it is important to elucidate the reactivity of each radical species with chemical compounds for understanding the efficacy of UV/chlorine AOPs. Table 2 summarizes reaction rate constants of HO˙, Cl˙, ClO˙, and Cl 2˙− with some chemicals reported in literatures [18,[24][25][26][27][28][29][30][31][32]. HO˙ has second-order reaction rate constants with approximately 10 9 -order level regardless of saturated compounds or benzene derivatives.…”
Section: Reactive Radical Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to elucidate the reactivity of each radical species with chemical compounds for understanding the efficacy of UV/chlorine AOPs. Table 2 summarizes reaction rate constants of HO˙, Cl˙, ClO˙, and Cl 2˙− with some chemicals reported in literatures [18,[24][25][26][27][28][29][30][31][32]. HO˙ has second-order reaction rate constants with approximately 10 9 -order level regardless of saturated compounds or benzene derivatives.…”
Section: Reactive Radical Speciesmentioning
confidence: 99%
“…An application of UV/NH 2 Cl process to 1,4-dioxane degradation revealed that Cl 2˙− and HO˙ mainly contributed to 1,4-dioxane degradation, and the reactivity of NH 2˙ was very limited [27]. Moreover, dissolved oxygen further decreased 1,4-dioxane degradation through the production of NO˙ that negligibly impacted 1,4-dioxane degradation.…”
Section: Uv/nh 2 CL Processmentioning
confidence: 99%
“…[8][9][10][11] The former is a disinfection by-product occurring ubiquitously in reclaimed wastewater, 9,12 while the latter is a common industrial 49 solvent often accidentally released into the sewer and the environment. 13 Both NDMA and 1,4-dioxane are probable carcinogens and thus are regulated in potable water reuse applications. The occurrences of NDMA in RO permeate intended for potable water reuse have occasionally been reported 14,15 at above the NDMA notification levels (10 ng/L) by the authority in California, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Some radicals in this group are more selective in reactivity (Guo et al ), but ·Cl, for example, may still play a significant role in this process (Wang et al , Wu et al ). Other literature suggests that ·Cl may be eventually transformed into ·OH (Chuang et al , Patton et al ).…”
mentioning
confidence: 99%